The interactive relationship between the dimensions of the requirements of economic intelligence and the strategic success of banks: Applied research on a sample of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of this research is to demonstrate the nature of the interactive relationship between the dimensions of the requirements of economic intelligence Represented by(Administrative and regulatory requirements, human requirements, and technical requirements) The strategic success of banks is represented by (Customer satisfaction, customer confidence, quality of service, growth) In three of the Iraqi banks own bank(Middle East Iraqi Investment, Al Ahli Iraqi, Gulf Commercial), The questionnaire was adopted as a tool for collecting data and information Of the sample (85) Who are they(Director of the Commissioner, M. Director Plenipotentiary, Director of Department, Director of Section, M. Section Manager, Division Officer, Unit Officer), The statistical program SPSS was used to calculate(Arithmetic mean, standard deviation, coefficient of variation, correlation coefficient, t-test, variance analysis), The research reached a number of conclusions, the most prominent of which are:• There is a correlation between the requirements of economic intelligence and strategic success• There are differences in the response of the sample around the paragraphs of the questionnaire according to the banks surveyed.